Determining the influence of plant-based proteins on the characteristics of dairy ice cream - Mykhalevych, Artur; Polishchuk, Galyna; Bandura (Kuzmyk), Uliana; Osmak (Fedchenko), Tetiana; Bass, Oksana (My University, 2024)
This paper investigates the functional and technolog-ical properties of proteins in the composition of dairy ice cream. The object of the research was the technology of ice cream with plant-based proteins. The problem to be solved was the improvement of physical-chemical and rheolog-ical characteristics of mixtures and ice cream with a low fat content by using moisture-binding structuring proteins of plant origin

У роботі досліджено функціональні та технологічні властивості білків у складі молочного морозива. Об’єктом дослідження була технологія морозива з білками рослинного походження. Вирішуваною задачею було покращення фізико-хімічних і реологічних характеристик сумішей і морозива з низьким вмістом жиру шляхом використання вологозв’язуючих структурних білків рослинного походження
Keywords: protein; soy isolate; low-fat ice cream; кафедра технології молока і молочних продуктів; білки; соєвий ізолят; низькожирне морозиво